Pengembangan Alat Praktikum Kalorimeter Bom pada Pokok Bahasan Kalor - safitri, Hesti nikmah; Masturi, Masturi; Edie, Sukiswo Supeni (UPEJ Unnes Physics Education Journal, 2018)
Calorific values were measured by bomb calorimeter on combustion in oxygen atmosphere. Bomb Calorimeter has been produced and researched in the world, because of its benefits on science. Parr Instrument Company is a company located in the USA which produced bomb calorimeter. In contrast to Indonesia, which has not research about it. This research aim to test for validity the bomb calorimeter that build before, and then applying to physics laboratory assistant’s students at university.  The bomb was completed by manual instruction, which tested for validity with the bomb. The methods was Research and Development (RnD) 4-D models that popularizes by Thiagarajan, which consists of four step: define, design, develop, and disseminate. The result of validity tools and manuals categorized as very decent, and applying this tool have very high response for students.